Musical Auditory Stimulation Influences Heart Rate Autonomic Responses to Endodontic Treatment - Ramos Santana, Milana Drumond (2017)
We aimed to evaluate the acute effect of musical auditory stimulation on heart rate autonomic regulation during endodontic treatment. The study included 50 subjects from either gender between 18 and 40 years old, diagnosed with irreversible pulpitis or pulp necrosis of the upper front teeth and endodontic treatment indication. HRV was recorded 10 minutes before (T1), during (T2), and immediately (T3 and T4) after endodontic treatment. The volunteers were randomly divided into two equal groups: exposed to music (during T2, T3, and T4) or not. We found no difference regarding salivary cortisol and anxiety score. In the group with musical stimulation heart rate decreased in T3 compared to T1 and mean RR interval increased in T2 and T3 compared to T1. SDNN and TINN indices decreased in T3 compared to T4, the RMSSD and SD1 increased in T4 compared to T1, the SD2 increased compared to T3, and LF (low frequency band) increased in T4 compared to T1 and T3. In the control group, only RMSSD and SD1 increased in T3 compared to T1. Musical auditory stimulation enhanced heart rate autonomic modulation during endodontic treatment.